2018
DOI: 10.1016/j.mjafi.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis among household women: A growing but neglected phenomenon

Abstract: This study shows that significant number of women had osteopenia/osteoporosis within 35-40 years age group. Intensive information, education, and communication activities with regard to osteoporosis causative factors and preventive measures targeted to household women may play an important role, if started at young age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…1,4 The same has been mentioned in the article as one of the limitation of the study and discussed. 5 We agree with the conclusion drawn by the reader that ''this particular study at best gives us an indication that there is an increased risk of fracture among this cohort of patient and there is a need for educating the target population regarding bone health and preventive measures. However, based on the data of QUS alone, it is premature to draw conclusion of increased osteoporosis or low bone mass in this cohort'' (sic).…”
supporting
confidence: 78%
“…1,4 The same has been mentioned in the article as one of the limitation of the study and discussed. 5 We agree with the conclusion drawn by the reader that ''this particular study at best gives us an indication that there is an increased risk of fracture among this cohort of patient and there is a need for educating the target population regarding bone health and preventive measures. However, based on the data of QUS alone, it is premature to draw conclusion of increased osteoporosis or low bone mass in this cohort'' (sic).…”
supporting
confidence: 78%
“…65 Unadjusted BMD data were not reported for 1 study. 66 Nine additional studies were excluded from this systematic review and meta-analysis because LS, FN, or WB BMD data were not presented; 5 of these studies measured BMD at the calcaneum, 61,[67][68][69][70] 3 measured it at the radius (mid and distal), [71][72][73] and 1 measured it at the proximal phalanx of the third finger. 74 Consequently, the final sample consisted of 20 articles (15 including BMD and 5 including fracture rate data) ( Figure 1).…”
Section: Search Summarymentioning
confidence: 99%
“…We found that the top five predictors were age, gender, disease history (DM, hypertension), and living habits (smoking). The results of Hiremath [28] uncovered that the risk increased by 20% with every 5 years increase of age. Besides, Fu et al [29] believed that the most people aged 45-50 may suffer from osteoporosis, which is almost a common feature of human aging, and the incidence of a fracture depends on the age of the subject.…”
Section: Establishment Of the Prediction Models For Osteoporosismentioning
confidence: 98%